UPAYA GURU PAI DALAM MEMOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN METODE PERMAINAN PADA MATA PELAJARAN PAI DI SMP ISLAM MAARIF 02 MALANG - Jalaludin Yahya; Azhar Haq; Nur Hasan (VICRATINA, 2019)
This study aims to describe the efforts of teachers in motivating students to learn with game methods and their supporting and inhibiting factors in Maarif 02 Islamic Middle School Malang. The problem faced is that there are some students who some students are less motivated in learning, bored, lazy, do not pay attention to the teacher's explanation so that the classroom atmosphere becomes less active. this study uses qualitative methods where documents are obtained based on the results of interviews, observation, and documentation. Which is analyzed by document reduction, document presentation conclusion drawing. The results of this study using the game method show that students' learning motivation increases in PAI subjects, students become active, changes in student behavior so that the classroom atmosphere becomes active and students want to be invited to work together by the teacher to achieve learning goals. Use the game method without having to leave other methods Keywords : teacher, learning motivation, game method